Meningkatkan Daya Saing Produk Lokal Desa Rebo Melalui Pendampingan Sertifikat Halal: Pengabdian - Christianingrum; Anggraeni Yunita; Jeanne D.N. Manik; Indah Novyanti; Erita Rosalina; Robert Tua Barasa; Tissa Aulia Damayanti; Marissa Pusparini (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Desa Rebo, rich in natural resources and local products, faces challenges in introducing these products to a wider market. One of the main obstacles is the lack of understanding and halal certification for the products produced by the village community. Halal certification is an essential standard that not only guarantees quality but also opens up broader market opportunities, particularly in the global market. Therefore, this community service aims to provide guidance to the residents of Desa Rebo in obtaining halal certification for their local products. The methods used in this activity include training, technical assistance, and consultations provided intensively to the BUMDes management and micro-entrepreneurs in the village. The expected outcome of this activity is an increase in the residents' understanding of the importance of halal certification and the achievement of halal certification for the village's flagship products. This outcome is expected to enhance the competitiveness of local products from Desa Rebo, expand market access, and ultimately improve the economic welfare of the local community. This program is crucial in promoting the village's economic independence through halal-certified and competitive products.